Construction Of An Automatic Clothesline System Based On An Arduino Uno Microcontroller Using A Rain Sensor And LDR - Nadia Fitri Ariska; Sri Cahaya Putri; Muhammad Alfarizi; Bayu Mangunsong (JURNAL TEKNISI, 2026)
Abstract: An Arduino Uno-based automatic clothesline is an automation system designed to help household activities protect clothes from weather changes, especially rain and dark conditions. This system uses an Arduino Uno as the main controller, a rain sensor to detect the presence of water, and a light sensor (LDR) to detect the intensity of ambient light. Data from the sensors is processed by the Arduino Uno to control a servo motor that functions to move the clothesline in or out automatically. The methods used in designing this system include the hardware design stage, programming, and system testing. Test results demonstrate that the servo motor consistently achieves a binary state of 1 (open) during bright conditions and 0 (closed) when sensors detect rain, darkness, or heavy rain . The system is able to work well, where the clothesline automatically moves in when it is detected to be raining or dark, and moves out when it is bright and not raining. With this system, it is hoped that it can increase efficiency, comfort, and the application of microcontroller technology in everyday life. Keyword: light dependent resistor (LDR); rain sensor; microcontroler   Abstrak: Jemuran otomatis berbasis Arduino Uno adalah sistem otomatisasi yang dirancang untuk membantu aktivitas rumah tangga melindungi pakaian dari perubahan cuaca, terutama hujan dan kondisi gelap. Sistem ini menggunakan Arduino Uno sebagai pengontrol utama, sensor hujan untuk mendeteksi keberadaan air, dan sensor cahaya (LDR) untuk mendeteksi intensitas cahaya sekitar. Data dari sensor diproses oleh Arduino Uno untuk mengontrol motor servo yang berfungsi untuk menggerakkan jemuran masuk atau keluar secara otomatis. Metode yang digunakan dalam mendesain sistem ini meliputi tahap desain perangkat keras, pemrograman, dan pengujian sistem. Hasil pengujian menunjukkan bahwa motor servo secara konsisten mencapai keadaan biner 1 (terbuka) selama kondisi terang dan 0 (tertutup) ketika sensor mendeteksi hujan, gelap, atau hujan deras. Sistem ini mampu bekerja dengan baik, di mana jemuran secara otomatis bergerak masuk ketika terdeteksi hujan atau gelap, dan bergerak keluar ketika terang dan tidak hujan. Dengan sistem ini, diharapkan dapat meningkatkan efisiensi, kenyamanan, dan penerapan teknologi mikrokontroler dalam kehidupan sehari-hari. Kata kunci: light dependent Resistor (LDR); sensor hujan; mikrokontroler